2000
DOI: 10.1021/ma0007029
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Behavior of Carboxymethylcellulose Hydrogels in Relation to Cross-Linking, pH, and Charge Density

Abstract: Hydrogels of carboxymethylcellulose (CMC) with 2.5%, 25%, 50%, and 100% cross-linking were prepared. Cross-linking and stoichiometry was controlled by appropriate addition of CMPJ and determined by potentiometric titration. The cross-linked polymer was then sulfated using a sulfur trioxidepyridine complex (SO 3-Py) in a heterogeneous mixture. Water uptake of the gels was studied in relation to cross-linking, pH, and sulfation. FT-IR spectra of the gels were recorded at different pHs to evidence the hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
183
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(196 citation statements)
references
References 22 publications
11
183
1
1
Order By: Relevance
“…Somewhat contrary results were reported by Barbucci et al (2000). Although these authors observed a monotonic decrease in swelling with increase in crosslinking up to a 50% level, they observed a higher swelling at "100% crosslinking".…”
Section: Crosslinkingcontrasting
confidence: 56%
See 2 more Smart Citations
“…Somewhat contrary results were reported by Barbucci et al (2000). Although these authors observed a monotonic decrease in swelling with increase in crosslinking up to a 50% level, they observed a higher swelling at "100% crosslinking".…”
Section: Crosslinkingcontrasting
confidence: 56%
“…As one might expect based on environmental concerns, many researchers have investigated the preparation of "all-natural-based" hydrogels incorporating cellulose or its derivatives (Harsh and Gehrke 1991;Barbucci et al 2000;Bin et al 2000;Fei et al 2000;Wach et al 2001Wach et al , 2002Hirsh and Spontak 2002;Liu et al 2002Liu et al , 2005aRodriguez et al 2003;Sannino et al 2003Sannino et al , 2004aSannino and Nicolais 2005;Yoshimura et al 2006;Demitri et al 2008;Faroongwang and Sukonrat 2008;Pourjavadi et al 2008Pourjavadi et al , 2010Chang et al 2009Chang et al , 2010Dai and Kadla 2009;El Salmawi and Ibrahim 2011;Salam et al 2011a,b;Wang et al 2011b;Kono and Fujita 2012;Pan and Ragauskas 2012;. For instance, a hydrogel based on a combination of cellulose and CMC can be prepared from a solution of the ingredients in a NaOH/urea solvent system .…”
Section: Hydrogels Based On Cellulose With Other Natural-based Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands at 1417 and 1319 cm −1 are for CH 2 scissors and OH bending vibration, respectively. The broad bands from 1000 to 1200 cm −1 were due to sugar ring absorption (Barbucci et al, 2000;Charpentier-Valenza et al, 2005). In the spectrum of ciprofloxacin hydrochloride (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Alginate, a linear polysaccharide (1-4) linked Lguluronic and D-mannuronic acid extracted from brown seaweed, can be ionic cross-linked by divalent or trivalent ions of both guluronic acid and mannuronic acid groups in the side chain leading to water-insoluble [4] Carboxymethyl cellulose (CMC), a hydrophilic anionic polymer derived from cellulose, enable water binding and moisture sorption properties due to its many hydroxyl and carboxylic groups. It can be chemical cross-linked using bifunctional crosslinking agent such as epichrolohydrin, formaldehyde and can be then swelled to form hydrogels and absorbs large amount of water [5,6].…”
Section: Introductionmentioning
confidence: 99%